Prognostic Value of Fluorine-18 Fluorodeoxyglucose Uptake of Bone Marrow on Positron Emission Tomography/Computed Tomography for Prediction of Disease Progression in Cervical Cancer. Issue 4 (1st May 2017) - Lee, Jeong Won; Jeon, Seob; Mun, Seong Taek; Lee, Sang Mi
Abstract : Objective: This study aimed to evaluate the prognostic value of fluorine-18 fluorodeoxyglucose (FDG) uptake of bone marrow (BM) on positron emission tomography (PET)/computed tomography in patients with uterine cervical cancer. Methods: One hundred forty-five patients with cervical cancer who underwent staging FDG PET/computed tomography and subsequent surgical resection or chemoradiotherapy were retrospectively enrolled in the study. Mean BM FDG uptake (BM standardized uptake value [SUV]) and BM-to-liver uptake ratio of FDG uptake (BLR) were measured. Relationships of BM SUV and BLR with hematologic and inflammatory markers were evaluated. Prognostic values of PET parameters for predicting disease progression-free survival and distant recurrence-free survival (DRFS) were assessed with a Cox proportional hazards regression model. Results: Bone marrow SUV and BLR were significantly correlated with white blood cell count and neutrophil-to-lymphocyte ratio. In the multivariate Cox regression analysis, International Federation of Gynecology and Obstetrics stage ( P = 0.048), neutrophil-to-lymphocyte ratio ( P = 0.028), platelet-to-lymphocyte ratio (PLR; P = 0.004), maximum SUV of cervical cancer ( P = 0.030), and BLR ( P = 0.031) were significantly associated with progression-free survival, whereas lymph node metastasis ( P = 0.041), PLR ( P = 0.002), and BLR ( P = 0.025) were significantly associated with DRFS. In a patient subgroup with chemoradiotherapy, BLR ( P = 0.044) was still an independent prognostic factor for predicting DRFS in multivariate analysis along with PLR ( P = 0.004). Conclusions: In patients with cervical cancer, BLR is associated with an increased risk of disease progression and distant recurrence.